Salidroside promotes rat spinal cord injury recovery by inhibiting inflammatory cytokine expression and NF‐κB and MAPK signaling pathways. Issue 8 (17th January 2019) - Su, Yiji; Zong, Shaohui; Wei, Chengming; Song, Fangming; Feng, Haotian; Qin, An; Lian, Zhen; Fu, Fangsheng; Shao, Siyuan; Fang, Fang; Wu, Tailai; Xu, Jiake; et al.
Abstract: Spinal cord injury (SCI) is a public health problem in the world. The SCI usually triggers an excessive inflammatory response that brings about a secondary tissue wreck leading to further cellular and organ dysfunction. Hence, there is great potential of reducing inflammation for therapeutic strategies of SCI. In this study, we aim to investigate if Salidroside (SAD) exerts an anti‐inflammatory effect and promotes recovery of motor function on SCI through suppressing nuclear factor‐κB (NF‐κB) and the mitogen‐activated protein kinase (MAPK) pathways. In vitro, real‐time polymerase chain reaction (PCR) and enzyme‐linked immunosorbent assay (ELISA) were used to examine the inhibitory effect of SAD on the expression and release of interleukin‐1β (IL‐1β), interleukin‐6 (IL‐6) and tumor necrosis factor‐α (TNF‐α) activated by lipopolysaccharide (LPS) in astrocytes. In addition, SAD was found to inhibit NF‐κB, p38 and extracellular‐regulated protein kinases (ERK) signaling pathways by western blot analysis. Further, in vivo study showed that SAD was able to improve hind limb motor function and reduce tissue damage accompanied by the suppressed expression of inflammatory cytokines IL‐1β, IL‐6, and TNF‐α. Overall, SAD could reduce the inflammatory response and promote motor function recovery in rats after SCI by inhibiting NF‐κB, p38, and ERK signaling pathways. Abstract : Salidroside (SAD) was found to inhibit nuclear factor‐κB, (NF‐κB) p38, and extracellular‐regulated protein kinases (ERK) signaling pathways by western blot analysis. Further, in vivo study showed that SAD was able to improve hind limb motor function and reduce tissue damage accompanied by the suppressed expression of inflammatory cytokines interleukin‐1β (IL‐1β), IL‐6, and tumor necrosis factor‐α (TNF‐α). Overall, SAD could reduce the inflammatory response and promote motor function recovery in rats after spinal cord injury by inhibiting NF‐κB, p38, and ERK signaling pathways.